2013
DOI: 10.1038/jid.2013.8
|View full text |Cite
|
Sign up to set email alerts
|

Thrombomodulin Regulates Keratinocyte Differentiation and Promotes Wound Healing

Abstract: The membrane glycoprotein thrombomodulin (TM) has been implicated in keratinocyte differentiation and wound healing, but its specific function remains undetermined. The epidermis-specific TM knockout mice were generated to investigate the function of TM in these biological processes. Primary cultured keratinocytes obtained from TM(lox/lox); K5-Cre mice, in which TM expression was abrogated, underwent abnormal differentiation in response to calcium induction. Poor epidermal differentiation, as evidenced by down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…In addition, local administration of recombinant TM (rTM) improved healing rates in the skin of TM-null mice. Hence they suggested that TM plays a critical role in skin differentiation and wound healing36. Previous studies also focused on the ability of TM to mediate anti-inflammatory effects via its lectin-like domain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, local administration of recombinant TM (rTM) improved healing rates in the skin of TM-null mice. Hence they suggested that TM plays a critical role in skin differentiation and wound healing36. Previous studies also focused on the ability of TM to mediate anti-inflammatory effects via its lectin-like domain.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous report suggested that sTM fragments released from keratinocytes promote cutaneous wound healing (Cheng et al, 2011). To evaluate more thoroughly the effects of TM on high-glucose-impaired wound healing, we used human rTMD23, which promotes wound healing in a manner similar to that of rTMD123 (Cheng et al, 2013), to treat high-glucose-maintained HaCaT cells. Using a scratch wound healing assay, we found that treatment with rTMD23 (20 and 200 ng ml − 1 ) significantly enhanced wound recovery at 72 hours after treatment (Figure 3a and b).…”
Section: Human Rtmd23 Improves Wound Healing and Ameliorates Tlr4 Dowmentioning
confidence: 99%
“…The protein structure of TM contains five functional domains from amino-to carboxyl-terminal, including the following: an NH 2 -terminal lectin-like region (TM domain (TMD)-1), an EGF-like domain consisting of six EGF-like repeats (TMD2), an O-glycosylation site-rich domain (TMD3), a transmembrane domain (TMD4), and a cytoplasmic tail (TMD5). Our studies have demonstrated that soluble TM (sTM) is released by the rhomboid serine protease, and recombinant TM domains 1, 2, plus 3, and 2 plus 3 (rTMD123 and rTMD23, respectively) may hold therapeutic potential to promote cutaneous wound healing (Cheng et al, 2013). In addition, circulating heterogeneous sTM fragments in the plasma are elevated in cardiovascular disease, inflammatory endothelial injuries, and diabetes (Ohlin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…TM is expressed in various cell types and exerts multiple biological functions via its different domains [8]. TM plays important roles in regulating blood coagulation, inflammation, and skin wound healing [8, 10]. Our earlier study showed that TM mediates cell-cell adhesion through its lectin-like domain [11].…”
Section: Introductionmentioning
confidence: 99%